Coronavirus Pandemic and Mental Health During Pregnancy: COVID-19 And Pregnants’ Mental Health - Naeiji, Zahra; Parsa, Yekta; Shokri, Nazila; Abbasi, Hajar; Behforouz, Athena; Nazemi, Sina; Moridi, Atefeh (International Clinical Neuroscience Journal, 2022)
Background: COVID-19 is an enveloped RNA virus, declared as a pandemic in 2020. The pandemic and the policies around it for controlling the infection have caused major psychological stress on the population, especially a high-risk group: the pregnant women. This study evaluates the anxiety and depression of pregnant women, in the first six months of COVID-19 pandemic in Iran. Methods: In this cross-sectional study, all pregnant women, visiting the obstetrics clinic of Mahdiyeh hospital, were enrolled in this study. Among them, women with no prior psychological disorder or use anti-anxiety or antidepressant drug were included in the study and were asked to complete the hospital anxiety and depression scale (HADS) questionnaire. Also, the demographic information, obstetrics history and past medical history of each patient were collected. Data were analyzed using SPSS software, version 22, using descriptive statistics (mean and standard deviation), t test, chi-square and Bonferroni post hoc tests. Significant levels were considered at P ≤ 0.05. Results: Overall, 465 pregnant women with a mean ± SD age of 26.75 ± 5.71 years were included in the study. The mean ± SD HADS score of the women was 12.00 ± 6.09 and 240 (51.6%) of the women had abnormal HADS score. Among the demographic properties, a significant association was seen between gravidity and HADS score (P < 0.05). Conclusion: COVID-19 can cause a considerable level of stress in women during their pregnancy, which can lead to adverse pregnancy outcomes. Among pregnant women, primigravida and multigravida (more than two previous pregnancy) ones were at higher risk of experiencing anxiety or depression.